Metrological requirements for biomedical device assessment and their ethical implications. (December 2022) - Costa Monteiro, Elisabeth; Summers, Ron
Abstract: Demands from the biomedical sector have challenged the existing international metrology infrastructure to provide traceable measurements comprising the sensing of physical, chemical, and biological quantities required for diagnostic and therapeutic processes. This paper explores the evolution of concerns expressed by metrology authorities regarding the provision of global metrological infrastructure to meet the demands for metrological traceability of biomedical measurement results, fostering the establishment of an appropriate regulatory framework that includes metrological requirements. A contribution from the viewpoint of underpinning ethical considerations is also addressed, along with a case study taken from biomagnetism.